Recommendations for return to sport during the SARS-CoV-2 pandemic. Issue 1 (13th July 2020) - Löllgen, Herbert; Bachl, Norbert; Papadopoulou, Theodora; Shafik, Andrew; Holloway, Graham; Vonbank, Karin; Jones, Nigel Edward; Bigard, Xavier; Niederseer, David; Meyer, Joachim; Muniz-Pardos, Borja; Debruyne, Andre; et al.
Abstract : In this viewpoint we make specific recommendations that can assist and make the return to sport/exercise as safe as possible for all those impacted – from the recreational athlete to the elite athlete. We acknowledge that there are varying rules and regulations around the world, not to mention the varying philosophies and numerous schools of thought as it relates to return to sport/exercise and we have been cognisant of this in our recommendations. Despite the varying rules and circumstances around the world, we believe it is essential to provide some helpful and consistent guidance for return to training and sport for sport and exercise physicians around the world at this most difficult time. The present viewpoint provides practical and medical recommendations on the resumption to sport process.